KONSENTRASI BELAJAR SISWA YANG SARAPAN PAGI DENGAN YANG TIDAK SARAPAN PAGI PADA MATA PELAJARAN F&B SERVICE - Sari, Citra Permata; Elida, Elida; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2013)
The purpose of this research is to analyze whether there are differences of the concentration of learning between the students who get breakfast and who miss breakfast, especially in the subjects F&B Service class X Jasa Boga SMK 9 Padang. This type of research is ex-postfacto with causal comparative form. The population in this study is 64 people from class X competency skills of Jasa Boga that have taken subjects F&B Service. The result of the research shows that, 61.5% of students who get breakfast have a high concentration level learning, 53.8% of students who miss breakfast lower concentration of learning and there are significant differences between the concentration of students who get breakfast with students who miss breakfast. The results showed that thitung 30 623 > ttable 2.8817 atÂ  Sig 0:05. It means that there is a difference between the concentration of students who do not get breakfast with the student who get breakfast. The concentration of students who get breakfast are higher than students who miss it. Â  Kata kunci: konsentrasi belajar, sarapan pagi, f&b service